2017
DOI: 10.4102/ajod.v6i0.332
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory validity of the Aspects of Wheelchair Mobility Test as demonstrated by a comparison of four wheelchair types designed for use in low-resource areas

Abstract: BackgroundComparative effectiveness research on wheelchairs available in low-resource areas is needed to enable effective use of limited funds. Mobility on commonly encountered rolling environments is a key aspect of function. High variation in capacity among wheelchair users can mask changes in mobility because of wheelchair design. A repeated measures protocol in which the participants use one type of wheelchair and then another minimises the impact of individual variation.ObjectivesThe Aspects of Wheelchair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Study participants confirmed the importance of qualitative and quantitative data, as well as that of data that would provide information specific enough to enable responsive modification and design changes. In other questionnaires using a similar format, the visual analogue scale provides continuous quantitative data while the comments provide qualitative data that gives a reason behind the rating (Rispin et al 2013; Rispin et al 2017b). High discriminatory validity for the WIQ cannot be confirmed until a large study with multiple sets of 10 or more individuals in different types of wheelchairs is completed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study participants confirmed the importance of qualitative and quantitative data, as well as that of data that would provide information specific enough to enable responsive modification and design changes. In other questionnaires using a similar format, the visual analogue scale provides continuous quantitative data while the comments provide qualitative data that gives a reason behind the rating (Rispin et al 2013; Rispin et al 2017b). High discriminatory validity for the WIQ cannot be confirmed until a large study with multiple sets of 10 or more individuals in different types of wheelchairs is completed.…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, these are very sensitive to differences in wheelchair users’ capacity, resulting in any information on the interface being overwhelmed by wide differences in users’ capacity (Kirby et al 2004; Mills 2003; Mortenson, Miller & Miller-Pogar 2007; Rushton et al 2011; Stanley et al 2003). Other tools assess multiple factors together, such as maintenance condition and appropriateness, or combine multiple components into one score (Karmarkar, Collins & Cooper 2009) and consequently have low resolution for data that could result in responsive changes in the design of a specific wheelchair component (Rispin et al 2017b). To be useful for wheelchair modification and design changes, a tool must also have high discriminatory validity (Jerosch-Herold 2005; May 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The way in which the function of motion is performed depends on the type of wheelchair being used [1][2][3]. The basic classification of wheelchairs defines them as electric, manual, or hybrid wheelchairs [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As described in the accompanying article (Rispin, Hamm & Wee, 2017 ), the AWMT uses measured tracks on four rolling environments: rough, smooth, tight spaces and curbs. These are commonly encountered in low-resource settings and were thought likely to discriminate differences because of wheelchair design.…”
Section: Introductionmentioning
confidence: 99%